The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13229-019-0311-3
|View full text |Cite
|
Sign up to set email alerts
|

TSC patient-derived isogenic neural progenitor cells reveal altered early neurodevelopmental phenotypes and rapamycin-induced MNK-eIF4E signaling

Abstract: Background: Tuberous sclerosis complex (TSC) is a neurodevelopmental disorder with frequent occurrence of epilepsy, autism spectrum disorder (ASD), intellectual disability (ID), and tumors in multiple organs. The aberrant activation of mTORC1 in TSC has led to treatment with mTORC1 inhibitor rapamycin as a lifelong therapy for tumors, but TSC-associated neurocognitive manifestations remain unaffected by rapamycin. Methods: Here, we generated patient-specific, induced pluripotent stem cells (iPSCs) from a TSC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 75 publications
3
55
1
Order By: Relevance
“…This finding is supported by prior experimental studies in a Tsc1 knockout mice, which has shown that dendritic patterning is modulated in an mTOR-independent manner through mitogen-activated protein kinases (MEK) that regulate phosphorylation of extracellular signal-regulated kinases (ERK). 2,9 The MEK-ERK was shown to be aberrantly activated in SEGAs, 8 and a similar activation and elevation of phosphorylated ERK (pERK) was noticed in the current study. Interestingly, pretreatment with rapamycin, while blocking mTORC1 activation, led to a significant increase in pERK1/2 in TSC-Het and Null and it was abolished by an application of MEK inhibitor trametinib.…”
Section: Commentarysupporting
confidence: 85%
“…This finding is supported by prior experimental studies in a Tsc1 knockout mice, which has shown that dendritic patterning is modulated in an mTOR-independent manner through mitogen-activated protein kinases (MEK) that regulate phosphorylation of extracellular signal-regulated kinases (ERK). 2,9 The MEK-ERK was shown to be aberrantly activated in SEGAs, 8 and a similar activation and elevation of phosphorylated ERK (pERK) was noticed in the current study. Interestingly, pretreatment with rapamycin, while blocking mTORC1 activation, led to a significant increase in pERK1/2 in TSC-Het and Null and it was abolished by an application of MEK inhibitor trametinib.…”
Section: Commentarysupporting
confidence: 85%
“…Previous studies showed that while the involvement of rapamycin in TSC2 patients control tumour growth, its efficacy in managing neuropsychiatric-associated behaviour in TSC2 patients has remained unclear [49]. Rapamycin failed to reverse the enhanced proliferation and altered neurite outgrowth; phenotypes inherent to TSC KO NPCs [50]. As rapamycin only particularly rescues the TSC2 neuronal phenotype, having little effect on the network deficit, we targeted aberrant synchronicity and connectivity deficits with alternative approaches via upstream TSC activation or by manipulating the mTORC1 at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the effectiveness of rapamycin in control tumour growth for TSC2 patients, its e cacy in managing neuropsychiatric-associated behaviour in TSC2 patients has remained unclear [45]. In a report, rapamycin also failed to reverse the enhanced proliferation and altered neurite outgrowth; phenotypes inherent to TSC KO NPCs [46]. As rapamycin had little effect on the network de cit, we targeted the aberrant synchronicity and connectivity de cits with alternative approaches, examining upstream TSC activation or downstream manipulation the mTORC1 at the molecular level.…”
Section: Discussionmentioning
confidence: 98%